Phthalates bioconcentration in the soft corals: Inter- and intra- species differences and ecological aspects. (June 2022) - Isa, Valerio; Saliu, Francesco; Bises, Chiara; Vencato, Sara; Raguso, Clarissa; Montano, Simone; Lasagni, Marina; Lavorano, Silvia; Clemenza, Massimiliano; Galli, Paolo
Abstract: The bioconcentration of dimethyl phthalate (DMP) diethyl phthalate (DEP) dibutyl phthalate (DBP) butyl benzyl phthalate (BBzP), di-(2-ethy hexyl) phthalates (DEHP), mono-butyl phthalate (MBP), mono-benzyl phthalate (MBzP), mono-(2-ethy hexyl) phthalate (MEHP) in the soft corals Coelogorgia palmosa, Sinularia sp., Sarcophyton glaucum, and Lobophytum sp. was investigated. Specimens were cultured in a microcosm environment built-up at the Genova Aquarium and analyses were carried out by in vivo SPME-LC-MS/MS. The distributions of the phthalates among the four surveyed species resulted significantly different. Calculated bioconcentration factors (BCFs) showed values spanning over two orders of magnitude, from a minimum of log10 BCFDEP = 1.0 in Sarcophyton glaucum to a maximum of log10 BCFDBP = 3, 9 calculated for Coelogorgia palmosa . Moreover, the calculated BCFs of the long chain phthalates resulted up to three orders of magnitude lower than theoretically predicted (from logK ow ), whereas BCF of short chain phthalates resulted higher. This, together with the detection of phthalic acid monoesters, suggests the presence of species-specific different metabolic transformation among the surveyed soft coral species that involve DEHP. Graphical abstract: Image 1 Highlights: The bioconcentration of phthalates has been evaluated in four alcyonacean species. The analysis of phthalates was carried out by employing in vivo SPME technique. All measured BCFs deviated from theoretical values calculated from K ow . The differences in terms of BCF among the surveyed species were also observed. Phthalates metabolism resulted to be species-specific.